MODERN APPROACHES TO ELIMINATING GRAMMATICAL INTERFERENCE IN GRADES 10–11 (Web of Teachers: Inderscience Research, 2025)
This article analyzes cases of grammatical interference in English language lessons and presents modern methodological approaches to address them. It specifically explores the types of interference that arise when transitioning from the native language to English, along with their causes and spheres of influence. Based on experimental research, the article recommends effective strategies to reduce grammatical interference.